COVID-19-Induced Downsizing and Survivors’ Syndrome: The Moderating Role of Transformational Leadership - Samreen, Farah; Nagi, Sadaf; Naseem, Rabia; Gul, Habib (Frontiers in Psychology, 2022)
Downsizing due to COVID-19 (COV-DS) and its consequences on laid-off employees has attracted the attention of many researchers, around the globe. However, the underlying mechanisms that explain the effects of COV-DS on the employees who have survived cutoffs remain underexplored. Grounded in the conservation of resources theory, this paper aims to study the causal path through which COV-DS reduces the survivors’ affective commitment. The current study proposes the mediation of survivors’ job uncertainty stress and organizational identification between COV-DS and survivors’ affective commitment. This study also posits the moderating role of transformational leadership between COV-DS and both the mediators. The extant study has employed WARP PLS 7 and Hayes Process Macro to test the hypothesized relationships. Using the sample of 274 employees from the private sector of Pakistan it was found that job uncertainty stress strongly mediates the relationship between COV-DS and survivors’ affective commitment. While, mediation of survivors’ organizational identification was not proved to be significant. However, with the moderation of transformational leadership both the mediators were proved to be significant.